 It is currently 18 Mar 2019, 16:09 ### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

#### Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here. # (x + 3)(y − 4) = 0  Question banks Downloads My Bookmarks Reviews Important topics
Author Message
TAGS: Moderator  Joined: 18 Apr 2015
Posts: 5811
Followers: 93

Kudos [?]: 1138  , given: 5418

(x + 3)(y − 4) = 0 [#permalink]
2
KUDOS
Expert's post 00:00

Question Stats: 48% (00:36) correct 51% (00:31) wrong based on 56 sessions
(x + 3)(y − 4) = 0

 Quantity A Quantity B xy −12

A)The quantity in Column A is greater.
B)The quantity in Column B is greater.
C)The two quantities are equal.
D)The relationship cannot be determined from the information given.

Practice Questions
Question: 6
Page: 466
Difficulty: medium/hard
[Reveal] Spoiler: OA

_________________ Moderator  Joined: 18 Apr 2015
Posts: 5811
Followers: 93

Kudos [?]: 1138  , given: 5418

Re: (x + 3)(y − 4) = 0 [#permalink]
2
KUDOS
Expert's post
Solution

At a first look, the question seems easy, but iondeed it is misleading and tricky

For two numbers being equal to zero one or both must be zero. From this, we do know that $$X=-3$$ and $$Y=4$$ or both.

Which means that if x=-3 y can take any value, ad the other way around. Or they can be just -3 and 4 AND from this we do have the same quantity -12.

You do have different answers.

The answer is $$D$$
_________________ GRE Instructor Joined: 10 Apr 2015
Posts: 1521
Followers: 55

Kudos [?]: 1449  , given: 8

Re: (x + 3)(y − 4) = 0 [#permalink]
3
KUDOS
Expert's post
Carcass wrote:
(x + 3)(y − 4) = 0

 Quantity A Quantity B xy −12

A)The quantity in Column A is greater.
B)The quantity in Column B is greater.
C)The two quantities are equal.
D)The relationship cannot be determined from the information given.

Given: (x + 3)(y − 4) = 0
This tells us that EITHER x = -3 OR y = 4

So, for example, if x = -3 and y = ANY number, the equation (x + 3)(y − 4) = 0 holds true.

So, one possible solution to the equation (x + 3)(y − 4) = 0 is x = -3 and y = 0
We get:
QUANTITY A: xy = (-3)(0) = 0
QUANTITY B: -12
In this case QUANTITY A is greater

Another possible solution to the equation (x + 3)(y − 4) = 0 is x = -11 and y = 4
We get:
QUANTITY A: xy = (-11)(4) = -44
QUANTITY B: -12
In this case QUANTITY B is greater

Another possible solution to the equation (x + 3)(y − 4) = 0 is x = -3 and y = 4
We get:
QUANTITY A: xy = (-3)(4) = -12
QUANTITY B: -12
In this case QUANTITY A = QUANTITY B

Cheers,
Brent
_________________

Brent Hanneson – Creator of greenlighttestprep.com Sign up for our free GRE Question of the Day emails Intern Joined: 11 Jan 2018
Posts: 44
Followers: 0

Kudos [?]: 33  , given: 7

Re: (x + 3)(y − 4) = 0 [#permalink]
1
KUDOS
It's a good question.

According to the question,
EITHER x + 3 = 0 or y - 4 = 0 or both equals 0.

So EITHER x = -3 or y = 4 or both possible.

We need an exact values of both x and y, but here if x = -3, then y can be used infinite values to satisfy the equation (x + 3)(y − 4) = 0

Similarly, if y = 4 is used, then x can be used infinite values to satisfy the equation (x + 3)(y − 4) = 0

So, Answer D is correct.
_________________

Persistence >>>>>>> Success

Don't say thanks, just give KUDOS.
1 kudos = 1000 Thanks Intern Joined: 23 Nov 2017
Posts: 45
Followers: 0

Kudos [?]: 45  , given: 0

Re: (x + 3)(y − 4) = 0 [#permalink]
2
KUDOS
This is deffinatelly meant to trick people.

You basically have two terms being multiplied by each ther that equal zero. For this to be true, at least ONE OF THE TERMS HAS TO BE ZERO. For that to occur, either x = -3 or y = 4. Since only one term needs to be zero, the other term and its variable can litterally be anything. You hence have no way of knowing what one of the variables will be. Manager Joined: 22 Feb 2018
Posts: 158
Followers: 2

Kudos [?]: 100  , given: 21

Re: (x + 3)(y − 4) = 0 [#permalink]
1
KUDOS
(x + 3)(y − 4) = 0
this equation equals 0 just when :
x = -3 and y = whatever or x = whatever and y = 4
so xy can be -3y or 4x while x or y can be whatever and thus they can be less or more or equal to -12. so the correct answer is D.

_________________

Manager  Joined: 26 Jun 2017
Posts: 104
Followers: 0

Kudos [?]: 39 , given: 38

Re: (x + 3)(y − 4) = 0 [#permalink]
yeah good question for those who just consume concepts without noticing logic behind them.
_________________

What you think, you become. Re: (x + 3)(y − 4) = 0   [#permalink] 03 Mar 2018, 23:45
Display posts from previous: Sort by

# (x + 3)(y − 4) = 0  Question banks Downloads My Bookmarks Reviews Important topics Powered by phpBB © phpBB Group Kindly note that the GRE® test is a registered trademark of the Educational Testing Service®, and this site has neither been reviewed nor endorsed by ETS®.